Progress of Backlight Devices: Emergence of Halide Perovskite Quantum Dots/Nanomaterials - Singh, Rajan Kumar; Chen, Li-Hsuan; Singh, Anupriya; Jain, Neha; Singh, Jai; Lu, Chung-Hsin (Frontiers in Nanotechnology, 2022)
The technology behind the display is becoming ever more prevalent in our daily lives. It has many applications, including smartphones, tablets, desktop monitors, TVs, and augmented reality/virtual reality devices. The display technology has progressed drastically over the past decade, from the bulky cathode ray tube, it progressed to the flat panel displays. In the flat panel displays, the liquid crystal display (LCD) and organic light-emitting diodes (OLEDs) are the two dominant technologies. Nevertheless, due to low stability and color tunability OLEDs remain behind the LCDs. The LCD screen has a backlight, usually, a white LED, which comprises a blue LED covered with a red and green enhanced layer (color converting layers). Although, InP/CdSe QDs attracted a lot of attention due to their solution processability and better color gamut than the previous technologies. But, the complexity of their synthesis was still an obstacle in their commercialization. Later, the emergence of perovskite with highly intense and tunable PL emission, high color purity and low-cost synthesis route, attracted the attention of display researchers. Owing to the relatively higher performance of perovskite quantum dots (PQDs) as compared to bulk (3D) perovskite in backlit display devices, these PQDs are being used for high color contrast and bright display devices. Furthermore, the color gamut for PQDs was observed as 140% of the NTSC standard that is nearby the commercial OLED devices. In this review, we have discussed the progress of display technologies with a clear classification of the pros and cons of each technology. Also, the application of perovskite QD/nanomaterials in LCD backlit devices has been discussed and the future direction of further improvement in their stability and performance has been listed.